Digital analysis of rotated images - Alliney, S. (IEEE transactions on pattern analysis and machine intelligence, 1993)
The problem of estimating the relative rotations of two images taken from the same scene is considered, and a numerical method for computing such rotations is presented. The main features of the proposed method consist of the possibility of fast in-place computations with no preliminary interpolation of the data and a considerable precision for moderate rotation angles. The final estimate is performed with a least square criterion, but in the present case, even such computations can be substantially simplified. A detailed analysis shows that for practical applications, the influence of discretization errors does not affect, in a relevant way, the precision of the results; that is also confirmed by numerical experiments.< >